Analisis Aliran Daya Pada Sistem IEEE 26 Bus Modifikasi - Uspa, Alfian Rachmadana; Hidayat, Aldi Muhammad; Jodiansyah, Muhammad; Nurkholas, Rizky; -, Yudistira; Prabowo, Bayu Dwi; -, Muslimin (Teknik Elektro Universitas Lancang Kuning, 2025)
Power flow analysis is essential, especially in electrical network systems, to determine the power capacity of an electrical energy system that has reached its specified limits. A power flow study is an analysis of electrical power flow within an electrical system. The research method employs the IEEE power flow method with a modified 26-bus system, analyzing power losses and voltage drops at each busbar in the circuit using the Newton-Raphson method and MATLAB R2017a software. This study aims to analyze the power flow values, power losses, and voltage drops in a modified IEEE 26-bus system using MATLAB software with the Newton-Raphson method. The results of the discussion and simulation show that the total active power and reactive power are 126.3 MW and 637 MVR, respectively, and the active power and reactive power of the generator are 1292.715 MW and 677.251 MVAR, respectively. The largest voltage drop occurs on line 16 to 17 with a voltage drop of 10.04%, and the lowest on line 17 to 21 with a voltage drop of -8.29%. According to SPLN standards, the voltage drop has a tolerance of +5% and a minimum of -10%. Therefore, it can be concluded that the analysis of the modified 26-bus IEEE power system does not comply with PLN standards, specifically on line 16 to 17. The simulation results show the largest active power loss of 6,221 MW and reactive power loss of 25,132 MVAR. .